Tracing the historical trajectory of the concept of prediction in High-Energy Physics - Panoutsopoulos, Grigoris (Neusis, 2025)
The concept of prediction has always been a cornerstone of physics and numerous philosophical studies have focused on and discussed its epistemic value. Nevertheless, only a few of those studies have shown an interest in the dynamic role that prediction actually plays in scientific practice and in the changes that its value undergoes in different contexts. The main goal of this paper will be to historicize the shifting epistemic value and character of prediction in High Energy Physics (HEP), which are significantly influenced by the relationship, in each period, between theory, experimentation and instrumentation. We will focus on three different episodes from the history of HEP: the discovery of weak neutral currents in 1973, back when the Standard Model did not yet have the acceptance and the prestige within the experimental community that it would attain during the years that followed; the discovery of the W and Z bosons in 1983, when the SM was established as the “only game in town” in HEP; and the planning stage of the Large Hadron Collider (LHC), during the 1980s and 1990s, where the collider’s design delineated a rather independent trajectory from theory, unbound by specific predictions. These case studies will allow us to contemplate the role that predictions play in discovery procedures, in the construction of HEP infrastructures and also in the formulation and execution of the science policy of Big Science organizations such as CERN.